Accuracy and Prognosis Value of the Sequential Organ Failure Assessment Score Combined With C-Reactive Protein in Patients With Complicated Infective Endocarditis - Lin, Yaowang; Dong, Shaohong; Yuan, Jie; Yu, Danqing; Bei, Weijie; Chen, Ruimian; Qin, Haiyan (Frontiers in Medicine, 2021)
This study aimed to evaluate the accuracy and prognostic value of the sequential organ failure assessment (SOFA) score combined with C-reactive protein (CRP) in patients with complicated infective endocarditis (IE). A total of 246 consecutive patients with complicated IE were included in the multicentric prospective observational study. These patients were divided into four groups depending on the SOFA score and CRP optimal cutoff values (≥5 points and ≥17.6 mg/L, respectively), which were determined using the receiver operating characteristic analysis: low SOFA and low CRP (n = 83), low SOFA and high CRP (n = 87), high SOFA and low CRP (n = 25), and high SOFA and high CRP (n = 51). The primary endpoint was in-hospital death, and the secondary endpoint was long-time mortality, defined as subsequent readmission and 3-years mortality in the follow-up period. High SOFA score and high CRP were associated with approximately 29.410% (15/51) of higher incidence of in-hospital death with an area under the curve of 0.872. Multivariate analyses showed that age [odds ratio (OR) = 2.242, 1.142–4.401], neurological failure (Glasgow Coma Scale ≤ 12) (OR = 2.513, 1.041–4.224), Staphylococcus aureus (OR = 2.151, 1.252–4.513), SOFA ≥ 5 (OR = 9.320, 3.621–16.847), and surgical treatment (OR = 0.121, 0.031–0.342) were clinical predictors for in-hospital death. On following up for 12–36 months, SOFA ≥ 5 (p = 0.000) showed higher mortality. A high SOFA score combined with increased CRP levels is associated with in-hospital mortality. Also, SOFA score, but not CRP, predicts long-term mortality in complicated IE.